2023
DOI: 10.3390/agriculture13050947
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Assessment of Water and Nitrogen Use Efficiency in Rain-Fed Chickpea-Durum Wheat Intercropping Systems

Abstract: It is well known that multiple interactions can occur between nitrogen and water use, depending on climate, soil and crop characteristics, in crop growth and yield development. However, little is known about the simultaneous change in both water and N use efficiency (WUE and NUE) and their possible interactions in cereal–-legume intercropping systems. In order to advance our knowledge on the N and water facilitation mechanisms involved in the intercropping responses of N and water input co-limitations, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…Indeed, the higher precipitation during the January-April period would allow for better vegetative growth of the crops, resulting in higher yields. Similar findings have been reported by Kherif et al (2023) for sole crops and intercropping of chickpea and wheat, attributing higher yields to a better distribution of precipitation throughout the growing season. The variation in rainfall distribution could also explain the extremely low LAI values in site 3, where a severe drought period was reported during the vegetative growth phase despite relatively high total precipitation for the 2022 season.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Indeed, the higher precipitation during the January-April period would allow for better vegetative growth of the crops, resulting in higher yields. Similar findings have been reported by Kherif et al (2023) for sole crops and intercropping of chickpea and wheat, attributing higher yields to a better distribution of precipitation throughout the growing season. The variation in rainfall distribution could also explain the extremely low LAI values in site 3, where a severe drought period was reported during the vegetative growth phase despite relatively high total precipitation for the 2022 season.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding NUE and WUE during the 2021 seasons, we found that both NUE and WUE were generally higher for sole cropped barley, followed by the mixed crop. These results are in line with previous studies on cereal-legumes intercropping (Kherif et al 2023). The only exception was the NUE in site 3, where the sole cropped pea had the highest NUE value.…”
Section: ; Kherif Et Al 2020) In Intercropping Systems Two Major Proc...supporting
confidence: 93%
See 2 more Smart Citations
“…This agricultural practice is grounded in ecological principles, specifically facilitation and complementarity [6,8]. Furthermore, intercropping systems combining legumes and cereals are widely acknowledged as highly efficient cropping systems with the potential to optimize the utilization of resources, particularly nitrogen and water [10,11]. Moreover, these systems have demonstrated increased resilience to abiotic stressors, such as drought, and offer effective strategies for weed, pest, and disease management without relying on herbicides [12][13][14].…”
Section: Introductionmentioning
confidence: 99%